The achievement gap: The impact of between‐class attainment grouping on pupil attainment and educational equity over time. (20th September 2022) - Hodgen, Jeremy; Taylor, Becky; Francis, Becky; Craig, Nicole; Bretscher, Nicola; Tereshchenko, Antonina; Connolly, Paul; Mazenod, Anna
Abstract: Despite extensive research on attainment grouping, the impact of attainment grouping on pupil attainment remains poorly understood and contested. This paper presents evidence from a study conducted with 2944 12–13 year olds, from 76 schools in England, who were allocated to between‐class attainment groups ('setting') in English and mathematics over the first 2 years of secondary schooling. After controlling for prior attainment, pupils in the top set performed significantly better than pupils in the middle and bottom sets in both English and mathematics. The findings indicate a widening gap in attainment, especially in the case of English. Findings, especially in the case of mathematics, provide more evidence of a relative benefit for pupils placed in top sets than a relative detriment for those in bottom sets.